Analisis Pengaruh Profesionalisme Terhadap Komitmen Organisasi, Kepuasan Kerja,Prestasi Kerja Dan Keinginan Berpindah Bagi Tenaga Profesi Perawat (Studi Pada Rumah Sakit Islam Sultan Agung Semarang) - Sri Rahayuningsih (Conference In Business, Accounting, And Management (CBAM), 2012)
This research aimed to test and analyze the influence of the professionalism toward organizational commitment, working satisfaction, working achievement, and quitting pretention from the nurses of Sultan Agung Islamic Hospital. This research was done using survey method to 120 nurses of Islami Hospital Sultan Agunng Semarang. Sampling technique used was census method. To test the data, the writer used validity test through factor analysis, reliability test with Alpha Cronbach, classis assumption test, simple linear regression analysis, and t-test to test and prove research hypothesis.The validity of data collected was tested using factor analysis method and for its reliability was tested using alpha coefficient (Alpha Cronbach). The result was that all data were valid and reliable. The result of analysis and discussion showed that: (1) professionalism positively influenced organizational commitment. It means that the higher professionalism, the higher organizational commitment also; (2) professionalism positively influenced working satisfaction. It means that the higher professionalism, the higher working satisfaction also; (3) professionalism positively influenced working achievement. It means that the higher professionalism, the higher working achievement also; (4) professionalism positively influenced quitting pretention. It means that the higher professionalism, the higher quitting pretention also.Keywords: Â Â Â Professionalism, Organizational Commitment, Working Satisfaction, Working Achievement, and Quitting Pretention